Benih Mardeka in the Political Movement in East Sumatra, 1916–1923 (KEMANUSIAAN The Asian Journal of Humanities, 2021)
This study aims to explain the movements, relationships and roles of Benih Mardeka newspaper in the political movement in East Sumatra from the period 1916 to 1923. Political movements took place as a result of rapid developments in the early 20th century in East Sumatra into a prosperous plantation area. The movements were carried by organisations delivered through propaganda tools or media, namely newspapers. One of the newspapers that loudly voiced national movement and nationalism in East Sumatra was Benih Mardeka newspaper, which began to appear in 1916. This study uses historical methods that include heuristic, source criticism, interpretation and historiography. The results showed that many articles in Benih Mardeka frequently criticised the issues of colonialism and capitalism. Meanwhile, the poor life of plantation workers became propaganda material for Benih Mardeka in criticising colonial and self-government as well as capitalists, namely plantation companies. Benih Mardeka was also a mouthpiece or tool for Sarekat Islam in conveying the idea of nation and nationalism. Hence, it can be concluded that Benih Mardeka consistently gave the voice of national movement and nationalism in the political movement and the press in East Sumatra.